Chile : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Chile. (IMF Staff Country Reports; Country Report ;, 2021)
The Chilean economy has been hit by the pandemic while recovering from the social unrest in late 2019, requiring substantial adjustment of economic policies and the appropriate use of existing policy buffers. Following a sharp decline in mid-2020, economic activity started recovering in 2020H2 in the wake of ample policy stimulus. Inflation remains near the policy target, with inflation expectations anchored, and the current account balance has improved amid a sharp drop in imports and relatively resilient exports. Fiscal and monetary policies remain guided by the structural fiscal balance rule and the inflation-targeting framework, respectively. Beyond the pandemic-related risks, there is uncertainty stemming from a series of elections and the outcome of a New Constitution process-scheduled to finish in mid-2022-which are expected to shape the public discourse and influence the policy agenda.